Postoperative Pain Management in Neonatal Surgery: Evaluating the Role of Multimodal Analgesia - Pehlajani, Yogesh; Chandra Gupta, Kailash; Bokade, Soniya (Journal of Neonatal Surgery, 2025)
Background: Neonatal surgery poses significant challenges in postoperative pain management due to the immature nervous system, metabolic differences, and concerns regarding opioid-related adverse effects. Historically, neonates were undertreated for pain, but recent evidence highlights the need for adequate pain control to prevent long-term neurodevelopmental consequences. Objective: This study evaluates the role of multimodal analgesia in neonatal postoperative pain management by assessing pain scores, opioid consumption, hemodynamic stability, and incidence of adverse effects in a tertiary care setting. Methods: A prospective observational study was conducted over one year in the neonatal surgical unit of a tertiary care hospital in Central India. A total of 120 neonates undergoing major surgeries were included. Pain management incorporated systemic analgesics (paracetamol, opioids), regional anesthesia (caudal epidural, ilioinguinal-iliohypogastric nerve blocks), and adjuncts (swaddling, sucrose). Pain was assessed using the Neonatal Infant Pain Scale (NIPS) and Premature Infant Pain Profile (PIPP). Statistical analyses were performed using ANOVA and chi-square tests. Results: Multimodal analgesia significantly reduced pain scores compared to opioid monotherapy (NIPS: 2.1 ± 0.5 vs. 3.8 ± 0.7, p < 0.05; PIPP: 4.5 ± 1.2 vs. 7.3 ± 1.5, p < 0.05). Opioid consumption was 40% lower in neonates receiving regional anesthesia (0.15 ± 0.03 mg/kg vs. 0.25 ± 0.05 mg/kg, p < 0.001). Hemodynamic stability was better in the multimodal group (heart rate: 120 ± 10 bpm vs. 130 ± 12 bpm; mean arterial pressure: 45 ± 5 mmHg vs. 40 ± 6 mmHg). The incidence of opioid-related adverse effects was significantly lower in the multimodal group (respiratory depression: 5% vs. 18%, ileus: 7% vs. 22%, p < 0.01). Conclusion: Multimodal analgesia provides superior pain control, reduces opioid dependence, improves hemodynamic stability, and lowers opioid-related adverse effects in neonates undergoing major surgery. Future research should explore long-term neurodevelopmental outcomes and optimize multimodal protocols to enhance neonatal pain management practices.